Corporatisation in private hospitals sector in India - A case study from Maharashtra - Chakravarthi, Indira et al (Economic and Political Weekly)
Transformation in the Indian private hospitals sector is examined in Maharashtra, employing qualitative interviews, witness seminars, and desk research. Findings point to significant changes: hospitals viewed as businesses to yield profits; adoption of business strategies to ensure financial viability and returns; changes in not-for-profit and small hospitals; and consequences for institutional and medical practice. Policy shifts towards greater private sector involvement in health, industry advocacy, availability of insurance, and patient expectations drive these changes towards corporatisation, which is not just about the growth of corporate hospitals; it entails structural and behavioural changes across the healthcare sector solely favouring economic goals.- Reproduced
Keywords: Hospitals, Medical services, Private hospitals, Maharashtra